PENGEMBANGAN MEDIA PEMBELAJARAN ONLINE TERHADAP KEMAMPUAN KONEKSI MATEMATIS MAHASISWA - Diki Mulyana; Mochammad Taufan (Universitas Pekalongan, 2020)
This research aims to develop and produce a valid and practical online learning media to students' mathematical connection skills. Specific targets to be achieved in this research specifically to increase in the mathematical connection ability of students of the Wiralodara Indramayu University mathematics study program for the Secondary Education Mathematics Capita Selecta course. This goal is based on the problem that the learning media used during lectures is learning media that has not been developed by lecturers, preparing for the 4.0 revolution and online learning is one of the impacts of Covid-19. From these problems resulted in the low ability of students in mathematical connections of the Secondary Education Mathematics Capita Selecta course. This type of research is development research using the Plomp model which has four stages, (1) initial stage, (2) design stage, (3) realization and construction stage, and (4) testing, evaluation, and revision. Meanwhile, the device developed was the online learning media for the Secondary Education Mathematics Capita Selecta course. The development of learning media that has been compiled is then validated with validation sheet instruments by expert validators and the criteria are set until the criteria are valid. Limited trials with questionnaire sheet instrument student responses and lecturer responses in Secondary Education Mathematics Capita Selecta course to measure practicality. The data in this study were obtained through expert validation instrument sheets and questionnaires. To achieve valid and practical criteria, it is processed descriptively. The targeted output is to produce online learning media in mathematics education for learning secondary mathematics selective capita courses.